Psychology Reflected in Buddhism and Western Psychology: A Brief Elucidation - Rathnasiri Rathnayaka (Politeknik Negeri Bali, 2018)
This paper exposes in brief universally adoptable stance of Buddhist Psychology vs. western psychology and how Buddhist psychology is capable of interacting with modern psychology contributing to both theory and practice. Psychology was introduced to the western world several centuries after the advent of Buddhism. The primary resolution of Buddhist doctrine is to expose through the universal causes of suffering (dukkha) in the continuous existence of individual and the society disclosing the true nature of the phenomenal existence, individual and mind in order to get rid of the human predicament. Comprehensive and profound psychological expositions that deal with the root causes of mental disorders and problematic behaviors are adopted in ‘Buddhist Psychology and Psychotherapy’ and the Abhidhamma entails highly systematized psychological elaborations of mind. Although several psychoanalytical observations based on superficial causes experimented by defiled minded scientists have been introduced in western psychology in analysis, ‘Buddhist psychology’ revealed by the Impassionate One is based on the universal central teachings such as the three universal root causes, the three universal characteristics, the theories of Four Noble Truths, Dependent co-arising etc. Hence, the objective of this paper is to provide a brief elucidation of how psychology reflected in Buddhism overlooks western psychology.